Cocoa beans and liquor fingerprinting: A real case involving SSR profiling of CCN51 and "Nacional" varieties. (December 2020) - Stagnati, Lorenzo; Soffritti, Giovanna; Martino, Michelangelo; Bortolini, Cristian; Lanubile, Alessandra; Busconi, Matteo; Marocco, Adriano
Abstract: The worldwide demand for cocoa is rising but, in the supply chain, several cases of adulteration, usually of fine cocoa with bulk cocoa, are reported while industry requires cocoa stocks with constant aromas and quality. In cocoa chain, adulteration and lots misidentification can happen along the entire chain from the bean to the production of liquor. The availability of a DNA traceability system able to recognize the different cocoa varieties is something expected to have a big impact on cocoa sector. Several studies carried out at the laboratory level support the use of DNA in traceability but, clearly, the situation can change completely when moving from the lab to real cases. In the present paper, samples were recovered from big lots of beans and liquors provided by an Italian big brand. Two different cocoa types labelled as "Nacional" and "CCN51" from Ecuador have been examined; DNA was extracted from both beans and cocoa liquor and successfully amplified and examined by using cocoa reference SSR markers. Allele profiles revealed that "Nacional" is an admixture of several genotypes as confirmed also by single beans and leaves profiling. Contrary to Nacional, analyses suggest that CCN51 from Ecuador is characterised by a single diploid genotype. The comparison of CCN51 alleles with data present in databases revealed that misidentification is present also for this modern vegetatively propagated variety and that in different countries are present different CCN51. The production of artificial mixtures demonstrates that DNA markers are able to identify even small traces of unwanted genotypes. Finally, the results suggest that, while for Nacional DNA traceability is not feasible, because of the multigenotype nature of the variety, for CCN51 traceability is possible. However, before doing this, it is necessary to precisely define the genetic identity of CCN51 by comparing accessions coming from the different countries where it is present and cultivated. Highlights: First study of cocoa genetic traceability in real case scenario. DNA marker traceability is feasible in cocoa-chocolate production chain. It is possible to extract PCR-grade DNA from cocoa liquor. Nacional cocoa variety comprises several genotypes.